2019
DOI: 10.1021/acs.molpharmaceut.9b00047
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Targeting by Peptide-Decorated Gold Nanoparticles

Abstract: Cancer remains one of the most important challenges in biomedical sciences. Chemotherapeutic agents are very potent molecules that exhibit a significant level of toxicity in numerous tissues of the body, particularly in those characterized by high proliferative activity, such as the bone marrow. The scenario is even more complex in the case of the central nervous system, and in particular brain tumors, where the blood brain barrier limits the efficacy of drug therapies. Integrins, transmembrane proteins widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…Our approach of modifying the surface properties of GNPs would enable higher circulation time, as well as active targeting of tumor cells once they reach the tumor tissue. This hypothesis has been further supported by another in vivo study where GNPs decorated with an RGD-like peptide had a four-fold higher accumulation within the tumor compared to that of uncoated particles [56]. The safety and efficacy of a multiple dosing approach has been demonstrated using GNPs and has been found to increase particle accumulation in tumors [57].…”
Section: The Dynamics Of Gnp Distribution and Retention Within Tumor Tissues In Vivomentioning
confidence: 80%
“…Our approach of modifying the surface properties of GNPs would enable higher circulation time, as well as active targeting of tumor cells once they reach the tumor tissue. This hypothesis has been further supported by another in vivo study where GNPs decorated with an RGD-like peptide had a four-fold higher accumulation within the tumor compared to that of uncoated particles [56]. The safety and efficacy of a multiple dosing approach has been demonstrated using GNPs and has been found to increase particle accumulation in tumors [57].…”
Section: The Dynamics Of Gnp Distribution and Retention Within Tumor Tissues In Vivomentioning
confidence: 80%
“…The delivery issue is common to all types of particles, but it is mitigated by the characteristic of tumor cells to be easier penetrated by NPs than healthy cells, while being less vascularized and more corrugated tend to retain particles for longer time, thus the definition of enhanced penetration/retention (EPR) of tumors. Numerous studies had been focused in pointing out the NPs parameters which maximize the EPR effect [204,220,221], while other followed a more active targeting philosophy working on modifying the surface of particles with specific antigens or molecules able to interact with specific tumors [222][223][224].…”
Section: Delivery Routes Of Nanoparticles In Tumorsmentioning
confidence: 99%
“…However, as observed before for tumor cell internalization, nanoparticle covering may be of great importance to determine the number of nanoparticles that crosses the BBB. In fact, it was demonstrated that arginine-glycine-aspartic acid-like peptide decorated gold nanoparticles in brain tumor was 1.5-fold that of undecorated nanoparticles and 5-fold that of PEGylated nanoparticles [52]. Besides, the size of nanoparticles is also an important factor that influences the nanoparticle capacity of crossing the BBB.…”
Section: Discussionmentioning
confidence: 99%